Computed Tomography of the Normal Bovine Tarsus. (22nd April 2016) - Hagag, U.; Tawfiek, M.; Brehm, W.; Gerlach, K.
Summary: The objective of this study was to provide a detailed multiplanar computed tomographic (CT) anatomic reference for the bovine tarsus. The tarsal regions from twelve healthy adult cow cadavers were scanned in both soft and bone windows via a 16‐slice multidetector CT scanner. Tarsi were frozen at −20 o C and sectioned to 10‐mm‐thick slices in transverse, dorsal and sagittal planes respecting the imaging protocol. The frozen sections were cleaned and then photographed. Anatomic structures were identified, labelled and compared with the corresponding CT images. The sagittal plane was indispensable for evaluation of bone contours, the dorsal plane was valuable in examination of the collateral ligaments, and both were beneficial for assessment of the tarsal joint articulations. CT images allowed excellent delineation between the cortex and medulla of bones, and the trabecular structure was clearly depicted. The tarsal soft tissues showed variable shades of grey, and the synovial fluid was the lowest attenuated structure. This study provided full assessment of the clinically relevant anatomic structures of the bovine tarsal joint. This technique may be of value when results from other diagnostic imaging techniques are indecisive. Images presented in this study should serve as a basic CT reference and assist in the interpretation of various bovine tarsal pathology.